Determinan Pengungkapan Kebijakan Dividen : Studi Empiris Pada Perusahaan Makanan Dan Minuman Di BEI - Rinda Permata Sari; Ditya Wardana (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2024)
The research objective is to determine the effect of debt policy, firm size and investment opportunities on dividend policy. The research subjects included food and beverage companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021 with a total of 39 companies. The sampling technique was purposive sampling with a sample of 11 companies. The research data is secondary data. The research data analysis method uses multiple linear regression analysis using the classical hypothesis test and the t-test hypothesis test. The results showed that debt policy has a positive effect on dividend policy, firm size has a positive effect on dividend policy and investment opportunities have no effect on dividend policy.